ANALISIS STRATEGI PEMASARAN PRODUK SMARTPHONEVIVO DI TELEMARCO PADA INTERNATIONAL PLAZA PALEMBANG - Iin Hendrayani (P3M STIE Mulia Darma Pratama, 2021)
Research of marketing strategy of Vivo smartphone products has been done at Telemarco at the Palembang International Plaza (IP). The purpose of this study was to find out the marketing strategy of the Smartphone Vivo product at the Palembang International Plaza. This research is a type of descriptive research using the method of presenting qualitative data which is analyzed using the SWOT method by describing the object of research based on strengths, weaknesses, opportunities and threats. Data collection techniques are carried out by means of Library Research and Field Research through observation and interviews. The results obtained from this study are that there are three marketing strategies of Vivo Smartphone in Telemarco Company which have been implemented include product strategies that build brand image, pricing strategies include cash and credit purchases, promotional strategies in the form of advertisements in Television, Newspapers and Online media as well as promo brochures and gift giving. The marketing strategy that has been carried out by the Telemarco Company is basically in accordance with the results of the SWOT analysis conducted on Vivo Smartphone products which include elements of marketing mix strategies such as Produck, Price, Promotion, and Place. Suggestions that can be given by the author in this study, Vivo provides gifts to consumers and the ease of buying by installments or also giving discount prices to attract consumers to buy. Marketing strategy analysis needs to be done every year so that the company always gets a new alternative strategy that is more innovative so that the goal to reach market marketing leaders can be achieved.